2020
DOI: 10.1002/eji.201948409
|View full text |Cite
|
Sign up to set email alerts
|

IL‐17 regulates DC migration to the peribronchial LNs and allergen presentation in experimental allergic asthma

Abstract: IL-17 is associated with different phenotypes of asthma, however, it is not fully elucidated how it influences induction and maintenance of asthma and allergy. In order to determine the role of IL-17 in development of allergic asthma, we used IL-17A/F double KO (IL-17A/F KO) and WT mice with or without neutralization of IL-17 in an experimental allergic asthma model and analyzed airway hyperresponsiveness, lung inflammation, T helper cell polarization, and DCs influx and activation. We report that the absence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 66 publications
0
14
0
Order By: Relevance
“…In a double IL‐17A/F knock‐out mouse model, Jirmo et al. showed a reduced influx of dendritic cells into lungs and lung‐draining lymph nodes 38 . The authors concluded that IL‐17 enhances airway dendritic cell activation, migration, and function.…”
Section: Discussionmentioning
confidence: 99%
“…In a double IL‐17A/F knock‐out mouse model, Jirmo et al. showed a reduced influx of dendritic cells into lungs and lung‐draining lymph nodes 38 . The authors concluded that IL‐17 enhances airway dendritic cell activation, migration, and function.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study revealed that IL17A could induce nasal fibroblasts to produce thymic stromal lymphopoietin (TSLP), which promotes Th2 inflammation in AR ( 22 ). In addition, IL17A could regulate DC migration to the peribronchial lymph nodes and allergen presentation in experimental allergic asthma ( 23 ). These findings implied a close relationship between IL17A and AR in the Th2-biased cytokine microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…Recent researches focused on Th17 and IL-17 contribution to type 2 low asthma, which is usually present in severe and corticosteroid-resistant asthma phenotype (33). Increased levels of IL-17 have been found in lung specimens, BALF, sputum as well as in peripheral blood of patients with severe asthma (34)(35)(36). High levels of IL-17 in asthma regulates the expression of proinflammatory cytokines and neutrophilic chemokines (34).…”
Section: Th17 and Il-17 In Allergic Rhinitis And Allergic Asthmamentioning
confidence: 99%
“…Increased levels of IL-17 have been found in lung specimens, BALF, sputum as well as in peripheral blood of patients with severe asthma (34)(35)(36). High levels of IL-17 in asthma regulates the expression of proinflammatory cytokines and neutrophilic chemokines (34). The regulatory mechanisms of neutrophilic inflammation are not well understood.…”
Section: Th17 and Il-17 In Allergic Rhinitis And Allergic Asthmamentioning
confidence: 99%
See 1 more Smart Citation